Clima organizacional y desempeño laboral en la ONG Operación Bendición Internacional Perú ciudad de Iquitos año 2024 - Perea Vasquez, Nelly Jeannette (2025)
The setting for this research is the non-governmental organization (NGO) Operation Blessing International Peru, located at its headquarters in Iquitos in 2024. This nonprofit organization has been working to benefit several communities in our city. The main objective was to study two variables: organizational climate and job performance, to determine whether there is a correlation between them. The methodological design was quantitative, correlational, non-experimental, and cross-sectional. A survey was used as the data collection technique; to measure reliability, we applied Cronbach's alpha, obtaining 63.6% for organizational climate and 69.1% for job performance, considered reliable and very reliable on the scale, respectively. Then, to measure the correlation between the variables, we used Pearson's correlation values, obtaining 77.5%, indicating a very strong positive correlation, with a bilateral significance value of 0.024, demonstrating a statistically significant relationship between the variables. We conclude, based on the findings of this study, that there is a significant relationship between organizational climate and job performance at the Iquitos office of the NGO Operation Blessing International Peru. Therefore, we emphasize working toward a positive organizational climate in its Leadership, Motivation, and Reciprocity dimensions to optimize employee performance.